EVALUATING NANDINI RIVER WATER QUALITY: A SYSTEMATIC REVIEW OF PHYSICOCHEMICAL STUDIES - Dhande, Bhagyashri S; Narkhede , Rajendra S (International Journal of Membrane Science and Technology, 2023)
The quality of water is described to be the condition of the water, which includes the three basic forms of physical, chemical, and biological notions. Salinity, turbidity, the amount of dissolved oxygen and carbon dioxide, and microorganisms, herbicides, and pesticides along with the presence of heavy metals edit reminds to have a direct effect on the water quality. Because the universal solvent is a major factor affecting the lives of the humongous population of people, recognition of the quality of water is significantly important. Due to the fact that the presence of contaminants in water can directly lead to health issues such as reproductive problems, different kinds of neurological disorders, and gastrointestinal diseases, it is of vehement importance to understand the water quality. Nandini River flows through the Nashik city of Maharashtraand it is the tributary of the river Godavari which is is a vital source of water for the people of the Nashik region.Travelling from the heart of Nashik the river Nandini is faced with several issues related to its degrading water quality. Hence, the study sheds light onto the quality of water of the Nandini river, in terms of Physicochemical Studies.